Ultrastructural imaging biomarkers in diabetic macular edema: A major review - Sagnik Sen; Hagar Khalid; Prithviraj Udaya; Rajiv Raman; Ranjan Rajendram; Zein ElHousseini; Luke Nicholson; Naresh Babu Kannan; Kim Ramasamy; Thandavarayan Kumaragurupari (Indian Journal of Ophthalmology)
Diabetic macular edema (DME) is a vision-threatening complication of diabetic retinopathy and causes significant morbidity in patients. Anti-vascular endothelial growth factor (VEGF) agents are the mainstay of treatment for DME, with steroid implants being used for the treatment of anti-VEGF resistant eyes. Over the years, several classification systems have been devised to describe the patterns of DME using optical coherence tomography (OCT). With the advent of effective treatments, it has become imperative that imaging cues are not merely used for classifying the disease but also as biomarkers for prognostication of disease activity and treatment response. In this aspect, newer imaging findings such as hyperreflective dots, photoreceptor integrity, and disorganization of retinal inner layers have been characterized in detail by several authors. Macular perfusion analysis using OCT angiography is the latest in the armamentarium for imaging DME. In this narrative review, we have summarized all relevant literature related to the ultrastructural imaging-based biomarkers of DME and their correlation to treatment.